The Role of Networking in the Relationship between Entrepreneurial Training and Performance of Small and Medium Enterprises among Manufacturing Firms; Kenyan Context - Wachira, Wachuka; Ndemo, Bitange; Maalu, Jackson; Njihia, James (European Journal of Business and Strategic Management, 2024)
Purpose: Small and medium enterprises (SMEs) are the backbone of many economies worldwide through the creation of employment opportunities and wealth for entrepreneurs. The objective of this study was to determine the role of networking in the relationship between entrepreneurial training and performance of SMEs in the manufacturing sector in Nairobi County, Kenya. Methodology: The variables considered in this paper are entrepreneurial training conceptualized as an independent variable and anchored on human capital theory, networking as the intervening variable, anchored on social networking theory and SMEs performance as the dependent variable. The study used a descriptive research design and a positivist worldview. With the aid of key informants from these businesses, a semi-structured questionnaire was administered to 504 SMEs in Nairobi County's manufacturing sector. The data was analyzed using descriptive and inferential statistics, notably Pearson's Product Moment Correlation and regression analysis for hypotheses and other statistical tests. Findings: The study discovered that networking positively and statistically intervenes the relationship between entrepreneurial training and firm performance (R2=.805, p=0.00). Unique Contribution to Theory, Practice and Policy: The study makes the suggestion that, as manufacturing SMEs increasingly raise their profile in national economic planning, it is necessary to ensure that their long-term production and market expansion potential is given the most consideration possible. Such an approach demands a thorough strategic plan for the industry's future, in part due to the justifications provided earlier in the study.